Overexpression of MDR1 using a retroviral vector differentially regulates genes involved in detoxification and apoptosis and confers radioprotection - Maier, Patrick; Fleckenstein, Katharina; Li, Li; Maier-Laufs, Stephanie; Zeller, W. Jens; Baum, Christopher; Frühauf, Stefan; Herskind, Carsten; Wenz, Frederik (Radiation research, 2006)
Overexpression of P-glycoprotein (P-gp), the product of the MDR1 (multidrug resistance 1) gene, might complement chemotherapy and radiotherapy in the treatment of tumors. However, for safety and mechanistic reasons, it is important to know whether MDR1 overexpression influences the expression of other genes. Therefore, we analyzed differential gene expression in cells of the human lymphoblast cell line TK6 retrovirally transduced with MDR1 using the GeneChip Human Genome U133 Plus2.0 (Affymetrix). Sixty-one annotated genes showed a significant change in expression (P < 10(-4)) in MDR1-overexpressing cells compared to untransduced cells and cells transduced with a control virus expressing the neomycin phosphotransferase gene. Several genes coding for proteins involved in detoxification and exocytosis showed similar to 1.4-4-fold increases in transcript levels (e.g. ALDHIA, UNC13). Additionally, pro-apoptosis genes were down-regulated (e.g. twofold for CASP1, 2.5-fold for NALP7) with concomitant increased expression of the potential anti-apoptosis gene AKT3. In functional assays the influence of MDR1 overexpression on apoptosis signaling was further corroborated by showing reduced rates of apoptosis in response to irradiation in TK6 cells transduced with MDR1. In conclusion, the resistant phenotype of MDR1-mediated P-gp-overexpressing cells is associated with differential expression of genes coding for metabolic and apoptosis-related proteins. These results have important implications for understanding the mechanisms by which MDR1 gene therapy can protect normal tissues from radiation- or chemotherapy-induced damage during tumor treatment. (c) 2006 by Radiation Research Society.